Deadly Pursuit - Roger Spottiswoode; Sidney Poitier Tom Berenger Kirstie Alley Clancy Brown Richard Masur (ABD Walt Disney Video, 1988)
Sidney Poitier, one of film's most distinguished and acclaimed actors, returns to the screen after a decade-long absence in this must-see, action-filled thriller. When a cunning murderer vanishes into the rugged mountains of the Pacific Northwest, pursuing FBI agent Warren Stantin (Poitier) must exchange familiar city streets for unknown wilderness trails. Completely out of his element, Stantin is forced to enlist the aid of expert tracker Jonathan Knox (PLATOON'S Tom Berenger). It's a turbulent yet vital relationship they must maintain in order to survive ... and one that becomes increasingly desperate when Knox's girlfriend Sarah (Kirstie Alley) becomes the killer's latest hostage.
Languages : English, German, Italian
Subtitles : English, Turkish, German, Italian
Keywords: Action -- Drama